Religious Minorities and Struggle for Recognition - Monnot, Christophe (Social Inclusion, 2020)
Religious minorities are increasingly present in the public sphere. Often pointed out as a problem, we argue here that the establishment of these minorities in Western societies is happening through struggles for recognition. Communities or individuals belonging to different minorities are seeking recognition from the society in which they are living. In Section 1, we present, briefly, our perspective, which differs from the analyses generally presented in the sociology of religion in that it adopts a bottom-up perspective. In Section 2, we present and discuss articles dealing with case studies in the cities of Barcelona, Geneva, and Montreal. In Section 3, we discuss two articles that present a process of individualization of claims for recognition. Finally, we present an article that discusses the case of an unrecognized minority in the Turkish school system.